Heterotopic pancreas in Meckel's diverticulum in a 7-year-old child with intussusception and recurrent gastrointestinal bleeding: Case report and literature review focusing on diagnostic controversies - Guanà Riccardo; Bucci Valeria; Carbonaro Giulia; Cerrina Alessia; Ferrero Luisa; Teruzzi Elisabetta; Mussa Alessandro; Morra Isabella; Schleef Jürgen (Wolters Kluwer Medknow Publications, 2014)
Meckel's diverticulum, the most common congenital abnormality of the small intestine, may be associated to heterotopic pancreas, often diagnosed incidentally on histopathological examination. Intussusception affects infants between the ages of 5 and 9 months, but it may also occur in older children, teenagers and adults, and in some cases can be derived by a Meckel's diverticulum resulting in acute abdomen. We analyse the management and the recent literature on similar cases, describing diagnostic options. In May 2013, a 7-year-old girl admitted to our hospital with recurrent gastrointestinal bleeding, was discovered to have an ileoileal intussusception with a leading Meckel's diverticulum with heterotopic pancreatic tissue. This association is rare evidence in children and its proper management can be controversial, in particular from a diagnostic point of view. In such cases, preoperative radiological diagnosis can be only suspected in the presence of suggestive signs, more often depicted by ultrasound or computed tomography scan. During laparotomy an accurate exploration of all ileum is recommended, for the possibility to find others heterotopic segments.